2022
DOI: 10.3389/fonc.2022.1006131
|View full text |Cite
|
Sign up to set email alerts
|

JNK inhibitor IX restrains pancreatic cancer through p53 and p21

Abstract: Novel treatment options for pancreatic cancer are desperately needed. De-regulated kinases can be regularly detected in pancreatic cancer. Multiple pathway inhibitors were developed to exploit these features, among them selective inhibitors of the c-Jun N-terminal kinase isoforms 1 and 2 (JNK1 and 2). We evaluated the effectiveness of four different JNK inhibitors on pancreatic cancer cell lines. Cell mobility and migration were evaluated in scratch assay and Boyden chamber assay. Mechanism of cell death was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Liu et al (31) reported that the Zrt-Irt-like protein 4/zinc finger E-box-binding homeobox 1 axis mediated the resistance of pancreatic tumors to GEM via regulating JNK/c-Jun signaling. Shi et al (26) also demonstrated that IX, a JNK inhibitor, restrained PC via regulating p53 and p21. Therefore, inhibiting JNK/c-Jun signaling may be a practicable approach for alleviating the metastasis and chemoresistance of PC (26,32).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Liu et al (31) reported that the Zrt-Irt-like protein 4/zinc finger E-box-binding homeobox 1 axis mediated the resistance of pancreatic tumors to GEM via regulating JNK/c-Jun signaling. Shi et al (26) also demonstrated that IX, a JNK inhibitor, restrained PC via regulating p53 and p21. Therefore, inhibiting JNK/c-Jun signaling may be a practicable approach for alleviating the metastasis and chemoresistance of PC (26,32).…”
Section: Discussionmentioning
confidence: 98%
“…Shi et al (26) also demonstrated that IX, a JNK inhibitor, restrained PC via regulating p53 and p21. Therefore, inhibiting JNK/c-Jun signaling may be a practicable approach for alleviating the metastasis and chemoresistance of PC (26,32). In the present study, GPX3 overexpression significantly inhibited the activity of JNK/c-Jun signaling.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Table 4 shows the inhibitors of SMAD-interacting enzymes (Jun N-terminal kinase (JNK), p38 MAP kinase, AKT, TRAF6, RhoA, PKA) that control non-SMAD noncanonical TGF-β pathways [ 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 ]. A potential inhibitor, SP0016125, targets c-Jun N-terminal kinase (JNK) and stimulates TGF-β-induced apoptosis of the RBE human cholangiocarcinoma cell line [ 264 ].…”
Section: Non-smad Non-canonical Tgf-β Pathway Controlmentioning
confidence: 99%